A4D: Augmented Reality 4D System for Architecture and Building Construction - Dias, J.; Capó, A.; Carreras, J.; Galli, R.; Gamito, M. N. (Proc CONVR2003, “Conference on Construction Applications of Virtual Reality”, Virginia Tech, Blacksburg, Virginia, 2003)
A4D is a cooperative design system for AEC that integrates state-of-art technologies in the area of 3D Computer Graphics, Computer Vision, Augmented Reality, 4D Simulation, Human-Computer Interaction, Computer Supported Cooperative Work, Mobile Computing and Sensory Devices. A4D's objective is to help the Architectural, Engineering, and Construction (AEC) sectors to build more efficiently, accurately, with lesser costs, in a manner that is more planned, safer, easier, and humanized for all, by developing and introducing new augmented reality technologies and novel workplace design concepts in AEC. A4D supports the reality-virtuality continuum in AEC, by enhancing the real environment with fixed and mobile augmented reality, supported in wearable system elements, vision-based user and object tracking systems (currently for indoor usage) and multi-user virtual environment. A4D also integrates building construction project scheduling technology and supporting interactive 4D (3D+time) visualization and design. A4D developments aim and tackle high innovative research but their concepts shall not disregard relevant issues such as applicability, human-factor, and prospects on cost and time effectiveness improvements.